A topic modeling-based analysis of emerging mobility services for carbon emission reduction - Li, Yang; Lei, Yutian; Wu, Zezhou; Wang, Jiahao; Pei, Tianjia; Antwi-Afari, Maxwell Fordjour (Frontiers in Public Health, 2025)
IntroductionWith rising urbanization and global climate change, sustainable city development has become an urgent challenge. Emerging mobility services provide innovative solutions for sustainable city governance, bridging the gap between transportation demand and supply, alleviating city travel and reducing carbon emissions. However, further investigation is needed to ascertain the specific roles and potential enhancements that emerging mobility services could contribute to reducing carbon emissions.MethodsIn this study, a systematic search of the Web of Science Core Collection using relevant keywords yielded 431 articles. After screening, 225 articles were deemed relevant, meeting the following criteria: (1) the articles focused on emerging mobility services, and (2) they explored the relationship between these services, carbon emissions, and environmental impacts. These articles were then synthesized using the Potential Dirichlet Allocation Model.ResultsThis study identifies four key research questions using the Potential Dirichlet Allocation Model: “Emerging Mobility’s Environmental Impacts,” “Policy-Led Sustainable Mobility Services,” “User-Centric Mobility Services,” and “Cost-Benefit Analysis of Electrification.” Assessments of the theme strengths track their evolution over time, highlighting the increasing importance of policy-led development and user-centered optimization.DiscussionThe study has shown that emerging mobility services have the potential to reduce carbon emissions; however, the extent of this impact varies by region, service type, and other factors. Policy strategies play a crucial role in promoting the development of new and emerging transport services. These findings contribute to the sustainable development of these services, the reduction of carbon emissions, and the improvement of urban living conditions.